(untitled) (El Hilo de la Fabula, 2022)
This article aims to consider the relation between the literary discourse of Ignacio Aldecoa in his story «Young Sánchez» (1957) and its rewriting in the film of Mario Camus (1963). In this way, we highlight its poetic correspondence, understood in terms of narratological and lyrical equivalences. Thus, this work exposes the convergence between two stories that, at first sight, seem to diverge.